Demographic variables associated with perceived needs satisfaction among special education teachers in the Divison of City Schools, Manila - Hsiao, Chien-Wen (Nikki) (Animo Repository, 2003)
The study determines whether certain demographic variables are associated with perceived needs satisfaction among special education teachers in Manila. The researcher used the descriptive method of research. The questionnaire was the main instrument for gathering data. The researcher also conducted informal interviews with some special education teachers to verify and reinforce data obtained from responses to the questionnaire. Five public elementary schools were selected as participating institutions in this study. Known as Silahis Centers, these are regular schools with special education programs for various types of exceptional learners. These schools were M. Hizon Elementary School, P. Gomez Elementary School, P. Burgos Elementary School, Sta. Ana Elementary School, and Justo Lukban Elementary School. A total of 120 special education teachers were selected as respondents in this study. The questionnaire used was adapted from Baterna (1991). Content validation of the instrument was done by means of judgmental validation. Descriptive statistics as frequency distribution, weighted mean and Chi-square test were used in analysing and interpreting responses. From the findings of the study, the following conclusions were drawn: 1. The special education teachers are predominantly females, married and in middle-age. They are educationally prepared to handle children with special learning needs. They derived satisfaction and a sense of identification from teaching as manifested by their being able to spend the best years of their lives in teaching. 2. The special education teachers are very satisfied with most of the areas of their needs which may reflect effective delivery of special education services. 3. Satisfaction of physiological, safety, social, esteem and self-actualization needs of special education teachers vary according to that age.